Aspek Resiliensi pada tokoh Hiroshi dalam film Jepang Hōmuresu Chuugakusei karya Sutradara Tomoyuki Furumaya - Hasna, Chindy; Andari, Novi (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
Resilience is the ability to survive and adjust when facing difficult circumstances. In the Japanese movie “Hōmuresu Chuugakusei” by Tomoyuki Furumaya, the resilience aspect of Hiroshi's character is described. By using a literary psychology approach, this research uses a theoretical study of aspects of resilience according to Reivich and Shatte (2002). This research uses a qualitative descriptive method to analyze the dialogue with Japanese and Indonesian subtitles, and scenes that illustrate aspects of resilience. This research will collect resilience scenes in the film, research, analyze, explain and describe the aspects of resilience in the film. The results of the study stated that seven aspects of resilience were found in the data source, namely emotion regulation, impulse control, optimism, clausal analysis, empathy, self-efficacy, and achievement totaling 10 data. Hiroshi described the tendency of resilience aspects, especially from the aspects of impulse control and clausal analysis. This research shows that support from the surrounding environment and from the internal side contributed greatly to Hiroshi's ability to survive.